The foreign tourists’ satisfaction towards the service quality provided by travel agencies in Kota Kinabalu, Sabah / Raja Eddy Akhmar Raja Iza Akhmar - Raja Iza Akhmar, Raja Eddy Akhmar (2012)
Tourism is travel for recreational, leisure or business purposes. According to the World Tourism Organization (1995), they define tourist as people “travelling to and staying in places outside their usual environment for not more than one consecutive year for leisure.” Since nowadays it is an ease for us humans to get from one place to another, tourism has become one popular and global activity. Either for business or leisure purposes, people from all across the world drive, fly and cruise for hours or might be for days for the purpose of reaching their destinations of choice. This movement certainly will cause the visited countries to generate more in term of economic aspect, and along these lines it will definitely increase the standard of living as well. In Malaysia, the scenario is very similar. Tourism industry in Malaysia has becoming one of the major industry and a big contribution towards the Malaysian economy. According to the Malaysian Tourism statistic, in 2011 alone, there were 24.7 million foreign visitors came and visit our country which contributed RM 58.3 billion to the economy (Tourism Malaysia, 2012). Neighboring countries like Indonesia, Thailand and Singapore topped the chart for the most visiting travelers coming in, followed by Asian countries such as the East Asians and the Arab countries. Australia, New Zealand and even from the European countries also have been one of the main visitors that came to Malaysia in that particular year. Even with this satisfying figure, the amount of travelers coming in should be increased from time to time. To make this into a reality, the degree of satisfaction on the tourists that come here should be in the best possible level as it could possibly be. In order to develop tourist industry, tourist satisfaction has been a considerable goal for many countries. In fact, developing the tourist industry is the target of any government all over the world because it can generate GDP and jobs (Ehsan, 2012). Many of the tourists will hire agents to manage them once they have reached to their destinations. These travel agencies then may provide related services such as airlines, car rentals, cruise lines, hotels, railways and also package tours. With all these things arranged, the frivolous process can be skipped and then surely there will no doubts and worries towards the distinct foreign environments they may face such as safety issues, transportation and so on. Therefore, the only thing that the tourists have to do is just relax, enjoy the view and spend time with their love ones while the agents will handle the rest. There are many different options when selecting where to travel and what to do when you get there, there is also variety of choices when selecting the travel agency that will help the tourists designs their perfect vacation. When the tourists are looking for the perfect travel agency, it is important that they understand the basic types of travel agencies from which to choose and in terms of services they provide to the vacationer. Indeed, the best agent that can fulfill their duties well will resulted good degree of satisfaction towards the tourists. Customer satisfaction can be experienced in a variety of situations and connected to both goods and services. It is a highly personal assessment that is greatly affected by customer expectations. Satisfaction also is based on the customer’s experience of both contact with the organization (the “moment of truth” as it is called in business literature) and personal outcomes (Michael, 2007). This aspect which what going to create post-purchasing feelings and loyalty which eventually will cause the tourists to revisit the destination they went to. Thus, from this study, it will be covering upon the foreign tourists’ satisfaction towards the service quality provided by travel agencies in Kota Kinabalu, Sabah. This will be emphasizing upon how their degree of services are towards the visiting foreigners and what are the factors influencing the satisfaction level. Sabah is by far one of the most visited states in Malaysia by foreigners with 795,953 visitors from January to December 2011 (Sabah Tourism Board, 2012). With 87 registered travel agencies in Sabah which most of them are in the city of Kota Kinabalu. Therefore this study will show whether the services provided are up the standard required to create satisfaction towards the foreign tourists or vice versa.